Audience Perception of the YouTube Content Gocek BungTowel - Azis, Abdul; Utami, Sinta Dwi; Avis, Ridho; Armaylia, Ester (SAINTIS Publishing, 2024)
This study aims to examine how the audience perceives Bung Towel's content about Shin Tae-yong/STY and the Indonesian National Football Team on the YouTube channel Gocek BungTowel, from the perspective of the Uses and Gratifications theory. The appeal of the Gocek BungTowel content lies in the fact that its content is dominated by Bung Towel's criticisms of STY and Indonesian football. The research subjects are five informants who closely follow news about STY and Indonesian football,but come from diverse backgrounds. This diversity in background leads to varying perceptions of the Gocek BungTowel YouTube content. The study uses a qualitative approach with Miles and Huberman’s interactive model to analyze the data. The findings indicate that the Gocek BungTowel content successfully influences the audience in three main aspects of the Uses and Gratifications theory. The content provides a more critical perspective on Indonesian football. In addition, it raises a wide range of emotions from the audience, ranging from satisfaction to discomfort, and encourages the audience to engage more deeply in discussions about Indonesian football. This study also reveals that the main motives driving the audience to access Gocek BungTowel content are to gain new insights into Indonesian football and to seek entertainment.